Alternative Antimicrobials in the Turkey Industry Challenges and Perspectives - Ashley Gernat; Fernanda Santos; Jesse Grimes (German Journal of Veterinary Research)
Abstract Turkey producers are facing a changing world in that many consumers perceive one thing about food production while the truth may be something else. However, when it comes to consumer acceptance, which affects consumer purchasing behavior, perception has become reality. In this regard, in many cases and genre, the public perception of antibiotic use in turkey production can be generally negative. The truth that antibiotics and other antimicrobials can be beneficial to both turkeys and consumers is lost. Therefore, turkey producers are accepting the challenge to rear turkey flocks without growth promoting antibiotics or antimicrobials. In some cases and in some locales this has become the law. In other markets, consumer desires and purchasing habits are the driving force for change. Turkey producers are scrutinizing production practices to ascertain and provide the optimal environment for turkey production. In addition, alternatives to antibiotics are being developed, tested, evaluated, and used for turkey production in increasing frequency. These include, but not limited to, probiotics (Direct Fed Microbials), prebiotics, organic acids, essential oils, spices, and plant extracts. Turkey producers are developing use plans for these feed additives that, in most cases, are not the same as for antibiotic administration. Turkey producers have become proactive in developing these plans and are preparing to provide products of exceptional quality that will meet with consumer acceptance.